Genomic characterization of invasive Neisseria meningitidis in Spain (2011/12–2022/23): expansion of clonal complex 213 and the potential threat to 4CMenB vaccine strain coverage - Josep Roca-Grande; Alba Mir-Cros; Carmen Muñoz-Almagro; Mayli Lung; Alba Bellés-Bellés; Jordi Càmara; Emilia Cercenado; M. Ángeles Galán-Ladero; Andrea Martín-Nalda; Albert Moreno-Mingorance; Daniel Navarro de la Cruz; M. Ángeles Orellana; et al. (Emerging Microbes and Infections)
Invasive meningococcal disease (IMD) is associated with significant global morbidity and mortality and is addressed by conjugated polysaccharide and subcapsular vaccines. In Spain, data on 4CMenB vaccine strain coverage and antimicrobial susceptibility are limited. This study aimed to describe the genomic epidemiology, predict 4CMenB vaccine strain coverage, and assess antimicrobial susceptibility of 323 Neisseria meningitidis isolates causing IMD, collected from 57 Clinical Microbiology Laboratories in Spain over 12 years (2011/12–2022/23). Whole genome sequencing was performed to identify serogroup, clonal complex (cc), and antimicrobial resistance determinants. Vaccine strain coverage for serogroup B (MenB) isolates was predicted using the genetic Meningococcal Antigen Typing System approach. The most prevalent serogroups were B (57.9%), W (21.4%), C (10.4%), and Y (8.4%). MenB predominated throughout most seasons, except during the 2019/20 season when serogroup W peaked. Post-COVID-19 pandemic, MenB remained the most frequent (70.2%). Thirteen cc were identified among MenB isolates, with cc213 being the most prevalent (40.1%). Only 28.9% of MenB isolates were predicted to be covered by 4CMenB, with cc213 showing an exceptionally low coverage rate (5.3%) due to antigenic variants poorly targeted by the vaccine. Notably, cc213 was responsible for twice the proportion of MenB cases in 4CMenB-vaccinated versus unvaccinated. All isolates were susceptible to third generation cephalosporins, and 13.5% showed penicillin resistance. This study highlights the alarming prevalence of cc213 among MenB IMD cases in Spain and the limited 4CMenB coverage against this cc. The disproportionate representation of cc213 in vaccinated individuals underscores its potential to compromise vaccine effectiveness.